RME Berbasis Video Streaming untuk Meningkatkan Hasil Belajar Siswa Di SMP Darunnajah Wuluhan Jember - Achmad Ghozali; Tri Susilaningtyas; Fury Styo Siskawati (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2019)
Most students assume that mathematics is a complex subject and has a higher level of difficulty in its teaching. The subject of this study is the seventh grade students of Darunnajah Wuluhan Jember Middle School. Based on the existing problems in this study, a problem was formulated, namely how the process of implementing RME based on Video Streaming in Grade VII students of Darunnajah Wuluhan Middle School and whether RME based on Video Streaming could improve students’ learning outcomes. The results revealed that the students’ learning outcomes respective in Cycle I was 70.05% and Cycle II was 94.1%. Thus, it shows an increase of 11.8% in mathematics learning. It can be concluded that RME based on Video Streaming can improve students’ learning outcomes. Keywords: RME, Video Streaming